Perancangan Sistem Informasi Pengelolaan Parkir Di Fakultas Keguruan Dan Ilmu Pengetahuan Universitas Sebelas Maret Surakarta - Cahyanto, Yudi Adi; Naury, Chairullah; Hastomo, Mursid Dwi (Politeknik Harapan Bangsa Surakarta, 2024)
The problems that are often encountered in conventional parking systems include the unavailability of complete, informative and interactive parking information. The manual parking system usually uses two ticket papers for each vehicle, where one ticket paper is held by the vehicle owner and the other ticket paper is installed in the vehicle. If the ticket paper in the owner's vehicle is lost or someone who is not responsible deliberately exchanges the ticket paper, chaos will occur and of course this is the responsibility of the parking attendant. This manual parking system is considered less effective because it consumes energy and time. Based on the description of the background mentioned above, it can be formulated that the problem to be solved in this study is